Determining Factors Of Sharia Stock Returns With Bi Rate As A Moderating Variable - Nurjanah, Laila Nida; Khabib, Nur (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
Research regarding the factors influencing Shariah stock returns is essential due to the existing disparities where Shariah stock returns continue to exhibit fluctuations amidst the annual increase in the number of issuers and stock investors. The objective of this study is to ascertain the influence of Earnings per Share (EPS), Return on Equity (ROE), and Price to Book Value (PBV) on Shariah stock returns, moderated by the BI rate. The population for this research encompasses all companies listed on the JII for the period 2017-2022. The sampling technique employed is purposive sampling, resulting in a total sample size of 18 companies, yielding 108 observations over a span of 6 years. The data analysis technique utilized is Moderated Regression Analysis (MRA), conducted using Eviews 12 software. The findings of this study reveal that EPS and PBV exhibit a negative and significant impact on Shariah stock returns, while ROE demonstrates a positive and significant influence. The BI rate weakens the influence of ROE on Shariah stock returns, whereas it reinforces the effect of PBV on Shariah stock returns. However, the BI rate does not possess the capability to moderate the impact of EPS. It's important to note that this research is confined solely to companies listed on the JII, consequently suggesting the need for future studies to broaden the population, extend the research period, and incorporate additional variables that may potentially impact Shariah stock returns.